Tissue Regeneration without Stem Cell Transplantation: Self-Healing Potential from Ancestral Chemistry and Physical Energies - Federica Facchin; Eva Bianconi; Silvia Canaider; Valentina Basoli; Pier Mario Biava; Carlo Ventura (Stem Cells International)
The human body constantly regenerates after damage due to the self-renewing and differentiating properties of its resident stem cells. To recover the damaged tissues and regenerate functional organs, scientific research in the field of regenerative medicine is firmly trying to understand the molecular mechanisms through which the regenerative potential of stem cells may be unfolded into a clinical application. The finding that some organisms are capable of regenerative processes and the study of conserved evolutionary patterns in tissue regeneration may lead to the identification of natural molecules of ancestral species capable to extend their regenerative potential to human tissues. Such a possibility has also been strongly suggested as a result of the use of physical energies, such as electromagnetic fields and mechanical vibrations in human adult stem cells. Results from scientific studies on stem cell modulation confirm the possibility to afford a chemical manipulation of stem cell fate in vitro and pave the way to the use of natural molecules, as well as electromagnetic fields and mechanical vibrations to target human stem cells in their niche inside the body, enhancing human natural ability for self-healing.